Loess in Italy: Genesis, characteristics and occurrence - Costantini, Edoardo A. C.; Carnicelli, Stefano; Sauer, Daniela; Priori, Simone; Andreetta, Anna; Kadereit, Annette; Lorenzetti, Romina (Catena, 2018)
There is currently a renewed interest in loess genesis and occurrence in Italy. Well-known loess profiles in northern Italy have been re-examined, and previously unknown loess deposits in central and southern Italy have been reported. This work combines a meta-analysis of published data with new data, presented here for the first time, to provide the state of the art on the spatial distribution, characteristics, genesis, and deposition ages of loess in Italy. A database of 98 soil horizons from 91 soil profiles was created and made available. It stores information on soils formed from loess or containing layers that show admixture of loess. Soil data include the source of information, the topographic, geomorphological and geological setting, kind of parent material and land use, main soil horizon properties as described in the field, soil classification, particle size distribution and chemical data. Loess is reported from almost all regions of Italy. It is generally pedogenized throughout the entire loess body and forms the parent material of deep and complex soil profiles. The thickness of the loess deposits varies from a few decimeters to a few meters; pedogenesis and local reworking partially change the original loess characteristics. In this study, we propose a set of parameters that help recognizing loess in soils: particle size distribution and sorting, geomorphological setting, pedostratigraphic position, shape of the grains under optical and scanning electron microscope (SEM), and soil-micromorphological characteristics. The ages of the loess deposits range between 70kaBP and 18kaBP. There are also a number of samples that have been dated to the Holocene. The meta-analysis suggests that climate is not the only driver of loess deposition in Italy; geomorphological instability and human disturbance, as well as the influence of Saharan dust, most likely played major roles, too. This study demonstrates that loess is much more widespread in Italy than previously estimated. Yet, further research on the spatial and temporal distribution of loess deposition across the Mediterranean region is needed to better understand its genesis, sources and trajectories, periods of enhanced loess formation, and the role of loess deposits in ecosystem functioning and resilience.